All Days 1996
DOI: 10.2118/37079-ms
|View full text |Cite
|
Sign up to set email alerts
|

State-Of-The-Art Cuttings Transport in Horizontal Wellbores

Abstract: In the ever growing directional and horizontal drilling, hole cleaning is a common and costly problem. It can become particularly critical in the case of extended reach drilling, where larger and longer wellbores are drilled. During the past two decades, especially in the recent years, many laboratory studies as well as field observations have been directed to address the cuttings transport problem. This has resulted in better understanding of the subject, and some remedies to overcome the problems. Several co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…For a long time, many scholars has been studying the hole cleaning problems of complex structural wells, and some achievements were made. Considering some major achievements reviewed by Pilehavri et al [3], this paper made a brief summary of hole cleaning before 2000 years, and the latest experimental researches, CFD simulations, correlations and models, and future study needs in hole cleaning were mainly addressed.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, many scholars has been studying the hole cleaning problems of complex structural wells, and some achievements were made. Considering some major achievements reviewed by Pilehavri et al [3], this paper made a brief summary of hole cleaning before 2000 years, and the latest experimental researches, CFD simulations, correlations and models, and future study needs in hole cleaning were mainly addressed.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with experimental work of Peden et al [28] but contradicts the idea presented by Hyun et al [29] that less viscous fluid with high velocity under turbulent flow regime result in better cuttings transport performances. Pilehvari et al [30] recommended that turbulent flow regime in horizontal and highly deviated wells, regardless of the viscosity of the fluid, will lead to good cuttings transport. This shows that a decisive rheological property of the drilling fluid for the purpose of cuttings transport is not available.…”
Section: Cuttings Transport Efficiencymentioning
confidence: 99%
“…Inner pipe rotation enhances cutting transport but it is absent in coiled tubing application (Leising and Walton 1998, Kelessidis and Bandelis 2004, Li, Misselbrook et al 2008. Hole inclination angle has a profound influence on cutting transport (Larsen, Pilehvari et al 1997, Pilehvari, Azar et al 1999. For angles of inclination less than 10 degrees, cutting transport remains similar to vertical case.…”
Section: Introductionmentioning
confidence: 99%
“…(Martins and Santana 1992) experimentally showed that smaller cuttings (smallest tested size was 2 mm) are easier to erode than bigger ones. According to (Pilehvari, Azar et al 1999) and based on the results of experiments by (Larsen, Pilehvari et al 1997), small cuttings (0.1 in) are more difficult to remove than bigger cuttings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation